2018
DOI: 10.1093/nar/gky116
|View full text |Cite
|
Sign up to set email alerts
|

Turnover of aberrant pre-40S pre-ribosomal particles is initiated by a novel endonucleolytic decay pathway

Abstract: Ribosome biogenesis requires more than 200 trans-acting factors to achieve the correct production of the two mature ribosomal subunits. Here, we have identified Efg1 as a novel, nucleolar ribosome biogenesis factor in Saccharomyces cerevisiae that is directly linked to the surveillance of pre-40S particles. Depletion of Efg1 impairs early pre-rRNA processing, leading to a strong decrease in 18S rRNA and 40S subunit levels and an accumulation of the aberrant 23S rRNA. Using Efg1 as bait, we revealed a novel deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 46 publications
3
22
0
Order By: Relevance
“…Interestingly, in vivo crosslinking in human cells revealed direct interactions between DHX37 and U3 sequences that lie close to the 3ʹ hinge region, which is predicted to basepair with the 5ʹ ETS, implying that DHX37 may influence U3-5ʹ ETS interactions. Consistent with this, we observed that expression of catalytically inactive DHX37 impairs processing at the A' cleavage site in the 5ʹ ETS, a pre-rRNA cleavage event that has previously been shown to be sensitive to depletion of the U3-associated protein U3-55K (RRP9) [57]. Our complementation assays show that the catalytic activity of DHX37 is required for the conversion of the 21S pre-rRNA to 18SE, indicating that removal of the 5ʹ ETS and site 2 cleavage in ITS1 can take place but that subsequent processing of ITS1 is inhibited.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Interestingly, in vivo crosslinking in human cells revealed direct interactions between DHX37 and U3 sequences that lie close to the 3ʹ hinge region, which is predicted to basepair with the 5ʹ ETS, implying that DHX37 may influence U3-5ʹ ETS interactions. Consistent with this, we observed that expression of catalytically inactive DHX37 impairs processing at the A' cleavage site in the 5ʹ ETS, a pre-rRNA cleavage event that has previously been shown to be sensitive to depletion of the U3-associated protein U3-55K (RRP9) [57]. Our complementation assays show that the catalytic activity of DHX37 is required for the conversion of the 21S pre-rRNA to 18SE, indicating that removal of the 5ʹ ETS and site 2 cleavage in ITS1 can take place but that subsequent processing of ITS1 is inhibited.…”
Section: Discussionsupporting
confidence: 78%
“…Stalling of exonucleases at highly structured pre-rRNA sequences, or pre-rRNAbound ribosome biogenesis factors or ribosomal proteins may lead to formation of discrete pre-rRNA intermediates, and the diffuse nature of the 16S* intermediate, which often appears as two bands, suggests that this species may be heterogenous as would be expected if it is produced by exonucleolytic trimming. It is possible however, that during surveillance, the 18S rRNA sequence is first targeted by an endonuclease, as was recently reported in yeast [57]. In yeast, Utp24 cleaves the 18S rRNA sequence at nucleotide 618 (Q1 site) between helices 19 and 20, whereas the 5ʹ end of 38S* maps to helix 32 of the human 18S rRNA.…”
Section: Discussionmentioning
confidence: 91%
“…Alternative cleavages at either the A 2 or A 3 site were recently described in yeast (Choque et al, 2018). However, in contrast to Arabidopsis or mammalian cells, only cleavage at A 2 is productive in yeast.…”
Section: Processing Of Pre-rrna: Two Alternative Pathwaysmentioning
confidence: 99%
“…Cleavage at A 3 by RNase MRP results in the production of 23S rRNAs. These 23S rRNAs are targeted by Upt24, generating 11S and 17S rRNAs, which are subsequently degraded by TRAMP/Exosome (nonproductive A 3 pathway; Choque et al, 2018).…”
Section: Processing Of Pre-rrna: Two Alternative Pathwaysmentioning
confidence: 99%
“…4B), suggesting that the apparent lack of exosome recruitment in the Utp14 mutant particles does not result in a noticeable defect in degradation of 5 ′ -A 0 in these particles. For the Utp14-ΔN mutant, this discrepancy could explained if the RNA of the stalled particle was not cleaved at A 0 and instead subjected to 3 ′ -exonucleolytic degradation by the exosome and/or endonucleolytic cleavage by Utp24 at the recently identified Q site (Choque et al 2018). The accumulation of apparent degradation intermediates in this particle ( Fig.…”
Section: Rna Composition Of Wild-type and Mutant Utp14 Particlesmentioning
confidence: 97%